1987
DOI: 10.3382/ps.0660264
|View full text |Cite
|
Sign up to set email alerts
|

Gut Stasis in Chickens Infected with Eimeria

Abstract: The duration and locations of gut stasis were examined in chickens infected with either Eimeria acervulina or E. maxima. Gut passage time (GPT) was used to determine gut stasis. The location of feed retention was determined qualitatively and quantitatively. Infections with both species were associated with increased GPT from Days 5 to 13 postinoculation. Feed appeared to be retained in the crop and gizzard of infected birds when judged visually. However, measurements of total dry matter retained in various reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, more detailed experimental studies would be needed to determine the cause of this trend. Likewise, coccidia of the genus Eimeria are known to induce gut stasis (McKenzie et al 1987) and, on the other hand, depend on certain temperatures and humidity for the onset of sporulation after exiting the host (Graat et al 1994), the time of onset of which is essential for their propagation. Both these facts could be implied in the observed circadian rhythm, but further studies would be necessary for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…However, more detailed experimental studies would be needed to determine the cause of this trend. Likewise, coccidia of the genus Eimeria are known to induce gut stasis (McKenzie et al 1987) and, on the other hand, depend on certain temperatures and humidity for the onset of sporulation after exiting the host (Graat et al 1994), the time of onset of which is essential for their propagation. Both these facts could be implied in the observed circadian rhythm, but further studies would be necessary for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, significantly increased oocysts numbers were recorded in control group than those of administered with purified beta-glucans. The chickens in control groups were observed depressed, lethargic and dull with ruffled feather and irregular feed and water intake (Personal observations) that may lead to alteration in gut homeostasis, altered metabolism and lower body weight gains, (McKenzie et al, 1987;Adams et al, 1996;Kettunen et al, 2001). The pathogenic Eimeria species seriously affect the enteric microenvironment and ultimately cytokines production, which lead to physiological changes and increased hemorrhagic lesions (Allen, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that examining the gut passage time of barium sulfate as a biomarker provides an indication of intestinal motility [66]. In our investigation, in birds that were challenged and received the drinking water disinfectant, gut passage time was significantly reduced compared to those that received the drinking water disinfection alone.…”
Section: Discussionmentioning
confidence: 61%